Signes de Belgique. - Meuris, Jacques (Seoul : The National Museum of Contemporary Art, 1991)
Charlier, Jacques ; Claus, Christian ; Corillon, Patrick ; De La Fontaine, Jean ; Gilles, Stephan ; Hubot, Bernard & Monika ; Le Docte, Philippe ; Lambotte, André ; Mahieu, Jean-Marie ; Mouffe, Michel ; Nyst, Daniele & Jacques-Louis ; Navez, Jean-Marc ; Ransonnet, Jean-Pierre ; Rouet, Christian ; Vandriesse, Cecile ; Wery, Marthe
Signes de Belgique, The National Museum of Contemporary Art, Seoul, 18.10. - 24.11.1991
boek
Keywords: België